Prevalence and Risk Factors Associated with Gastritis in Patients Visiting Royal Prima Hospital - Zulkifli Adnan; Maya Sari Mutia; Tan Suyono (Professional Health Journal)
Introduction:  Gastritis is an inflammation of the stomach lining caused by Helicobacter pylori and can be acute or chronic. This bacteria colonizes the stomach of more than 50% of humans and causes disease. Gastritis still has a high prevalence and if left untreated can lead to serious complications, such as gastric ulcers, bleeding, and even gastric cancer.